Synthesis of PtIV‐Biomolecule Conjugates through Click Chemistry. Issue 32 (26th October 2015) - Gabano, Elisabetta; Ravera, Mauro; Tinello, Stefano; Osella, Domenico
Abstract: The azide‐functionalized Pt IV complex {( OC ‐6–34)‐chlorido(cyclobutane‐1, 1′‐dicarboxylato)(cyclohexane‐1 R, 2 R ‐diamine)[2‐hydroxyethyl(2‐{2‐[2‐(2‐azidoethoxy)ethoxy]ethoxy}ethyl)carbamate]platinum(IV)} was synthesized and characterized to obtain a starting complex that was suitable for coupling with appropriate biological carriers in a drug targeting and delivery strategy. The following click reaction (Cu I ‐catalyzed Huisgen cycloaddition, CuAAC) was successfully applied for coupling with three different model biomolecules that can be exploited for selective targeting of the platinum conjugate toward tumor cells; i.e., the amino acid alanine and the dipeptide lysine‐alanine, both previously alkyne‐functionalized with pent‐4‐ynoic acid, and the hormone 17α‐ethynylestradiol. The title complex demonstrated very good compatibility with both CuAAC reaction and solid‐phase peptide synthesis conditions, making it a suitable antiproliferative fragment for the design of nanovectors. Abstract : Cu I ‐catalyzed Huisgen cycloaddition was applied to a new azide‐functionalized Pt IV complex for coupling with three different model molecules that can be exploited for selective targeting of the platinum conjugate toward tumor cells.